2018
DOI: 10.1186/s13104-018-3169-0
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in genes encoding penicillin-binding proteins in β-lactamase-negative ampicillin-resistant Haemophilus influenzae in Japan

Abstract: Objectiveβ-Lactamase-negative ampicillin-resistant Haemophilus influenzae is a common opportunistic pathogen of hospital- and community-acquired infections, harboring multiple single nucleotide polymorphisms in the ftsI gene, which codes for penicillin-binding protein-3. The objectives of this study were to perform comprehensive genetic analyses of whole regions of the penicillin-binding proteins in H. influenzae and to identify additional single nucleotide polymorphisms related to antibiotic resistance, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Two penicillin-binding proteins emerged as major determinants for resistance to ampicillin and first- and third-generation cephalosporins. These included a variant of PBP3 initially discovered in Haemophilus influenzae ( 43 ) described as a pivotal component of the cell division complex ( 44 ) and AmpH, which is involved in peptidoglycan recycling ( 45 ). Chromosomally encoded AmpC proteins were the first enzymes reported to degrade penicillin ( 46 ) and conferred resistance to ampicillin, 1GC, and 3GC.…”
Section: Discussionmentioning
confidence: 99%
“…Two penicillin-binding proteins emerged as major determinants for resistance to ampicillin and first- and third-generation cephalosporins. These included a variant of PBP3 initially discovered in Haemophilus influenzae ( 43 ) described as a pivotal component of the cell division complex ( 44 ) and AmpH, which is involved in peptidoglycan recycling ( 45 ). Chromosomally encoded AmpC proteins were the first enzymes reported to degrade penicillin ( 46 ) and conferred resistance to ampicillin, 1GC, and 3GC.…”
Section: Discussionmentioning
confidence: 99%
“…Initially we identified the genes of resistance to β-lactam antibiotics in 19 ESBL-producers compared to 17 ESBL-negative isolates. The same amino acid substitutions S357N and D350N in PBP3 encoded by the ftsI gene ( Misawa et al, 2018 ), were found in all MDR NTS isolates, regardless of the ESBL-production phenotype. Interestingly, four strains with these substitutions were sensitive to all β-lactams tested.…”
Section: Discussionmentioning
confidence: 84%
“…As determined by bioinformatics analysis of WGS data, all 19 ESBL-positive isolates possessed the common β-lactam resistance mechanisms. According to CARD, these included the bla CTX–M– 5 gene and two amino acid substitutions, S357N and D350N, in penicillin binding protein 3 (PBP3), which is encoded by the ftsI gene ( Misawa et al, 2018 ) ( Table 2 ). In four isolates (4/19, 21.05%), in addition to the common β-lactam resistance mechanisms, the bla OXA– 1 gene was identified.…”
Section: Resultsmentioning
confidence: 99%
“…2). Every isolate had a pair of fosfomycin resistance-related mutations in the glpT and uhpT transporters (21) as well as a pmrF gene associated with resistance to polymyxin antibiotics (22), a Penicillin-binding protein (PBP) 3 gene (23), and a bacA gene (associated with low-level resistance to bacitracin) (24). Additionally, there were 16 efflux components and determinants associated with their expression, including general efflux regulators such as H-NS histone-like protein (25) and cpxA (26).…”
Section: Resultsmentioning
confidence: 99%